Attitudes Toward Cognitive Enhancement: The Role of Metaphor and Context. Issue 1 (2nd January 2019) - Conrad, Erin C.; Humphries, Stacey; Chatterjee, Anjan
Abstract : The widespread use of stimulants among healthy individuals to improve cognition has received growing attention; however, public attitudes toward this practice are not well understood. We determined the effect of framing metaphors and context of use on public opinion toward cognitive enhancement. We recruited 3, 727 participants from the United States to complete three surveys using Amazon's Mechanical Turk between April and July 2017. Participants read vignettes describing an individual using cognitive enhancement, varying framing metaphors (fuel versus steroid), and context of use (athletes versus students versus employees). The main outcome measure was the difference in respondent-assigned level of acceptability of the use of cognitive enhancement by others and by themselves between the contrasting vignettes. Participants were more likely to support the use of cognitive enhancement by others than by themselves and more when the use of enhancement by others was framed with a fuel metaphor than with a steroid metaphor. Metaphoric framing did not affect participants' attitudes toward their own use. Participants supported the use of enhancement by employees more than by students or athletes. These results are discussed in relation to existing ethical and policy literature.